2011
DOI: 10.1007/s00384-011-1367-5
|View full text |Cite
|
Sign up to set email alerts
|

DNA promoter methylation status and protein expression of interleukin-8 in human colorectal adenocarcinomas

Abstract: BackgroundInterleukin-8 (IL-8) also referred to as CXCL8, a member of the CXC chemokine family that attracts neutrophils and other leukocytes, has been associated with cancer. Angiogenesis is a prime regulator of tumour expansion and data support that IL-8 is a potent angiogenic factor. Epigenomic instability has been postulated to play a role for the development of multiple neoplasias including colorectal cancer (CRC). DNA methylation of cytosine residues in CpG dinucleotides leads to transcriptional silencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…However, in contrast to the elucidation of the cis element and trans factors involved in the transcriptional control of this gene, the evidence for the participation of epigenetic mechanisms was only partially revealed, and contrasting results were sometimes obtained. In this regard, a marked CpG hypomethylation of the IL-8 promoter has been detected in human colorectal adenocarcinomas 29 and in aggressive and chronic periodontitis, 30 , 31 whereas other studies have proved that atypical methylation pattern of the IL-8 promoter strongly correlates with an increase in IL-8 expression and the metastatic potential of breast carcinoma cells 32 . A larger number of studies have been conducted to determine histone modifications associated with IL-8 gene expression following a variety of stimuli, such as LPS in intestinal epithelial cells, 33 leptin in synovial fibroblast cells, 34 UVR in keratinocytes 35 and Moraxella catarrhalis in bronchial epithelial cells 36 .…”
Section: Discussionmentioning
confidence: 97%
“…However, in contrast to the elucidation of the cis element and trans factors involved in the transcriptional control of this gene, the evidence for the participation of epigenetic mechanisms was only partially revealed, and contrasting results were sometimes obtained. In this regard, a marked CpG hypomethylation of the IL-8 promoter has been detected in human colorectal adenocarcinomas 29 and in aggressive and chronic periodontitis, 30 , 31 whereas other studies have proved that atypical methylation pattern of the IL-8 promoter strongly correlates with an increase in IL-8 expression and the metastatic potential of breast carcinoma cells 32 . A larger number of studies have been conducted to determine histone modifications associated with IL-8 gene expression following a variety of stimuli, such as LPS in intestinal epithelial cells, 33 leptin in synovial fibroblast cells, 34 UVR in keratinocytes 35 and Moraxella catarrhalis in bronchial epithelial cells 36 .…”
Section: Discussionmentioning
confidence: 97%
“…The hypomethylated six CpG sites in the IL-8 promoter have been associated with renal cell carcinoma (Yoo et al, 2013). Earlier study have also shown the role of IL-8 methylation in oral epithelial cells of aggressive and chronic periodontitis and in human colorectal adenocarcinomas (Andia et al, 2010;Oliveira et al, 2009;Dimberg et al, 2012).…”
Section: Introductionmentioning
confidence: 92%
“…The bisulfite converted DNA was amplified using specific MSP primers (IL-8 MF (c-f), IL-8 MR(c-f), IL-8 UMF(cf) and IL-8 UMR(c-f) ( Table 2) (Dimberg et al, 2012). All the primers were synthesized commercially through IDT, USA.…”
Section: Methylation Specific Pcr (Msp)mentioning
confidence: 99%
“…Previous studies have shown that CXCL8 and its receptors, CXCR1 and CXCR2, were significantly upregulated in colorectal cancers and acted as regulators of proliferation, angiogenesis and metastasis (2-4). Dimberg et al (5) reported that high plasma levels of CXCL8 tend to be correlated with distant metastasis, indicating an advanced disease stage. Thus far, the serum level of CXCL8 in patients with breast carcinoma has not been investigated extensively.…”
Section: Introductionmentioning
confidence: 99%